Discharge of a Contract where Both Parties are in Breach: Alliance Concrete Singapore Pte Ltd v Comfort Resources Pte Ltd - THAM, Chee Ho (Institutional Knowledge at Singapore Management University, 2010)
This case note examines the most recent attempt by the Court of Appeal to provide further guidance on: (a) how the doctrine of discharge of contract by breach operates when both parties are in breach of their contract obligations; and (b) when a promisee is entitled to rely on an alternate basis to justify its election to discharge a contract for the promisor’s breach when the basis originally relied upon and communicated to the promisor is ultimately found to be legally insufficient.